Peningkatan Pengetahuan Konseptual Berorientasi HOTS Pada Mata Kuliah Pendidikan PKn SD Melalui Penerapan Case Method Berbantuan Quizizz Mahasiswa PGSD Universitas Bengkulu - Pebrian Tarmizi; Atika Susanti; Siti Wulandari; Ady Darmansyah (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2023)
This research aims to describe (1) the application of the Case Method assisted by Quizizz and (2) increasing HOTS-oriented conceptual knowledge in the Elementary Civics Education course for PGSD students at Bengkulu University. This research uses classroom action research, which is carried out in a cyclical design. Each cycle stage includes planning, implementation, observation, and reflection. The subjects of this research were 27 semester IVB students, consisting of two male students and 25 female students. Data collection techniques use observation, documentation and written tests. Data analysis was carried out by conducting qualitative data analysis and quantitative analysis. The application of the Case Method method with the help of Quizizz media is carried out with the main material of Forming Students' Character/Character by completing one case regarding sexual violence and bullying. The results of students' conceptual knowledge test scores in the pre-cycle showed an average score of 49.07 (less), there was an increase after implementing the Case Method assisted by Quizizz in cycle I to 53.89 (less), and again increased in cycle II to 78.52 (Good). The conclusion was that there was an increase in HOTS-oriented conceptual knowledge in the Elementary Civics Education course through the application of the Case Method assisted by Quizizz for PGSD students at Bengkulu University.